Fabrication of aquaponic gravity flow plantation system for lettuce plant - Amierul Amin, Abdul Aziz (2013)
This project was carried out to fabrication of aquaponic gravity flow plantation system for lettuce plant. The objectives of this project are to fabricate and reinforced the curved water tank for hydro plantation and to integrate the gravity flow plantation unit for aquaponic system. In this study, it is focus on the history development of aquaponic, why is so significant for future, types, technology, advantages, types of plantation, types of animals and vegetables and the significant of gravity flow design. The design generation and design selection have been shown in this report in order to select the best design concept of the gravity flow plantation system. The solid three dimensional structures modeling of the gravity flow plantation system has been developed by using the solid work software. Material selection and the factor of the selection also have been listed based on the appropriate criteria predetermined. A briefly explanation about the fabrication process for completing this project is also has been stated in this report. An improvement and recommendation of the fabrication of aquaponic gravity flow plantation system for lettuce plants is provided for further implication.